Integrated health and nutrition approaches to school feeding: maximising future human capital in Latin America and the Caribbean - Laura M. Irizarry; Marie Evane Tamagnan; Carla Mejía; Heidi Kessler; Sarah Grundahl Kohnstamm; Giulia Baldi (Frontiers in Public Health)
Integrated health and nutrition packages in schools have been shown to be a cost-effective approach to support children’s well-being and academic achievement; yet few countries adequately invest in promoting such integration. School feeding programmes in Latin America are among the best-established, with some of the largest scale and coverage in the world. National School Meal programmes in Latin America and the Caribbean benefit over 80.3 million children and adolescents in the region. This paper seeks to determine the level of integration of complementary activities to school meal programmes in the region by examining their determinant factors: objectives, complementary services, governing regulatory frameworks, and monitoring and evaluation mechanisms. Our review reveals that although most governments offer school meals together with at least one complementary health and/or nutrition intervention, multisectoral commitment and investment is lacking. Under the premise that most school meal programmes in Latin America and the Caribbean have the potential to maximize their impact by providing integrated packages that meet children’s health and nutrition needs, we provide recommendations and raise considerations for the revision of programmatic guidance and policies moving forward. This analysis is relevant to countries internationally and calls for a comparable analysis to be carried out to promote a wide-reaching exchange on the integration of complementary activities to school feeding programmes globally.